2018
DOI: 10.1111/acer.13626
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Manipulation of the Nucleus Accumbens Alters Binge‐Like Alcohol Drinking in Mice

Abstract: We conclude that the reduction in EtOH drinking is not due to general malaise, altered perception of taste, or reduced calorie-seeking. Furthermore, we provide the first evidence for bidirectional control of NAc core and binge-like drinking. These findings could have promising implications for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…Indeed, several recent studies have demonstrated that electrical activation of NAc via deep brain stimulation (DBS) can attenuate alcohol drinking in animals and reduce alcohol craving in human alcoholics. These data, along with the findings by Purohit and colleagues (), support the notion that sex may be a major factor for effective AUD treatments and should be incorporated as a biological variable into more alcohol drinking studies.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Indeed, several recent studies have demonstrated that electrical activation of NAc via deep brain stimulation (DBS) can attenuate alcohol drinking in animals and reduce alcohol craving in human alcoholics. These data, along with the findings by Purohit and colleagues (), support the notion that sex may be a major factor for effective AUD treatments and should be incorporated as a biological variable into more alcohol drinking studies.…”
supporting
confidence: 71%
“…However, the observation of depressed excitatory signaling in D2 neurons (or enhanced competition by D1 neurons) suggests that increasing activity of the NAc or D2 neurons exclusively may also reduce alcohol drinking behavior. In the May 2018 issue of ACER , Purohit and colleagues () demonstrated that enhancing the activity of NAc neurons with DREADDs reduced binge drinking in female mice. This finding, contrary to the results found in males from Cassataro and colleagues (), strongly suggests sex differences in how the NAc controls binge drinking.…”
mentioning
confidence: 99%
“…That is, in vivo chemogenetic manipulation of dMSN or iMSN via hM3Dq or hM4Di, mimicking glutamatergic or GABAergic enhancement, respectively, affected alcohol consumption with hM3Dq activation in dMSNs or hM4Di activation in iMSNs promoting alcohol consumption, and oppositely reducing consumption through hM3Dq activation in iMSNs or hM4Di in dMSNs (Cheng et al, 2017). Anatomically distinct functions of the NAc core and shell in alcohol consumption were revealed in a limited access mouse model where alcohol consumption was reduced or increased following hM3Dq or hM4Di stimulation, respectively, of the NAc core but not accumbal shell (Purohit et al, 2018). It has also been observed that activation of KORD in neurons projecting to the NAc from the ventral subiculum decreased context-induced relapse of alcohol self-administration (Marchant et al, 2016a).…”
Section: Addictionmentioning
confidence: 98%
“…Mice were serially treated with vehicle prior to DID during week 1 to establish baseline drinking, then vehicle or CNO during weeks 2-5 to measure the effects of chronic treatment, and then mice were treated with vehicle again during week 6 to determine whether there were any lasting effects of chronic CNO treatment. Ethanol intake was measured as described in Purohit at al., 2018 [29]. For neuronal morphology analysis, female HDID-1 mice (S34.G36; n = 4-5/fluid type/treatment) were deeply anesthetized 22 h after the last DID and transcardially perfused with 0.01 M PBS and 4% w/v paraformaldehyde (PFA).…”
Section: Methodsmentioning
confidence: 99%
“…Purina brand food (5LOD, PMI Nutrition International, Brentwood, MO, USA) was suspended in a wire-top, and food and water were available ad libitum. Female mice were used in experiments 1 and 2 to facilitate comparison with data our group had previously published in C57BL/6J mice [29]. Male and female mice were used in experiment 3.…”
Section: Introductionmentioning
confidence: 99%